Evaluation of reproductive hormones and histological of ovary in female rats treatment with dexamethasone - Talib Al-Muswie, Rana (University of Thi-Qar Journal of Science, 2017)
The present study aimed to investigate the effect of dexamethasone Concentration on reproductive hormones and histochange of ovary in female’s rats. Twenty four adult female rats (Rattus norvegicus) were used. They were divided into four groups, (6) rats for each group. The first group (A) treated with normal saline for three months as a control group, the second group (B) treated with low dose dexamethasone (10 mg/kg/day) for three months, the third group(C) treated with intermediate dose dexamethasone for three months (20 mg/kg/day), and the fourth group (D) treated with high dose dexamethasone (40 mg/kg/day) for three months. The result indicated a significant increase in FSH and LH levels in all treated groups with dexamethasone (B, C and D) groups compared with control group. Also, there was a significant increase in FSH and LH levels in group B compared with C and D groups, with a significant increase in C compare with D (table 1 and 2). The results of histological change in ovary showed effect on all the follicles stimulation in group(B,C) treated with low doses and mid doses compare with control group and hyperplasia of theca and granulosa cells of ovarian treated with high doses groups (D) sections for three month, when compared with control group which show normal histological features . The study concludes that the abuse of dexamethasone caused side effect to woman which used it.